“The world is in Amsterdam”: Amsterdam, the Netherlands, and the Dutch in Guinevere Glasfurd’s The Words in My Hand - Žárská, Lenka (American & British Studies Annual, 2021)
The article presents an imagological study of the recent historical novel The Words in My Hand (2016) by British author Guinevere Glasfurd with the focus on how the Dutch and the 17th century Netherlands are portrayed in the novel, especially regarding the use of stereotypes. After offering an introduction into how the Dutch were perceived by the English in the 17th century, the article goes on to argue that Glasfurd makes use of both historical and contemporary stereotypes in order to highlight the personal traits of the characters and create sympathies and antipathies in the reader. To do so, she not only employs stereotypes about the Dutch and their country, but frequently uses France as its superior counterpart. Thusly, she contributes to a larger discourse of literature which relies on the use of national stereotypes and perceives the nation and national character as perceptible actuality rather than a changing social concept.